24.7k views
1 vote
6 · 14 - (9 + 8)2 =

User Weldabar
by
5.2k points

2 Answers

4 votes
166 I’m not sure I did the equation fast
User Rick Roy
by
6.3k points
7 votes
6 * 14 - (9 + 8)2 = 50

First, do the parentheses:

9 + 8 = 17

Your new equation would then be 6 * 14 - 17 * 2

Then multiply starting from left to right:

6 * 14 = 84
17 * 2 = 34

Your new equation would then be 84 - 34

Now subtract:

84 - 34 = 50

There you go! If you have any more questions feel free to comment! :D
User Djfm
by
5.9k points